Model‐based lamotrigine clearance changes during pregnancy: clinical implication - Polepally, Akshanth R.; Pennell, Page B.; Brundage, Richard C.; Stowe, Zachary N.; Newport, Donald J.; Viguera, Adele C.; Ritchie, James C.; Birnbaum, Angela K. (Annals of clinical and translational neurology, 2014)
Objective The objective of the study was to characterize changes in the oral clearance (CL/F) of lamotrigine (LTG) over the course of pregnancy and the postpartum period through a model‐based approach incorporating clinical characteristics that may influence CL/F, in support of developing clinical management guidelines. Methods Women receiving LTG therapy who were pregnant or planning pregnancy were enrolled. Maternal blood samples were collected at each visit. A pharmacokinetic analysis was performed using a population‐based, nonlinear, mixed‐effects model. Results A total of 600 LTG concentrations from 60 women (64 pregnancies) were included. The baseline LTG CL/F was 2.16 L/h with a between‐subject variability of 40.6%. The influence of pregnancy on CL/F was described by gestational week. Two subpopulations of women emerged based on the rate of increase in LTG CL/F during pregnancy. The gestational age‐associated increase in CL/F displayed a 10‐fold higher rate in 77% of the women (0.118 L/h per week) compared to 23% (0.0115 L/h per week). The between‐subject variability in these slopes was 43.0%. The increased CL/F at delivery declined to baseline values with a half‐life of 0.55 weeks. Interpretation The majority of women had a substantial increase in CL/F from 2.16 to 6.88 L/h by the end of pregnancy, whereas 23% of women had a minimal increase. An increase in CL/F may correspond to decreases in LTG blood concentrations necessitating the need for more frequent dosage adjustments and closer monitoring in some pregnant women with epilepsy. Postpartum doses should be tapered to preconception dose ranges within 3 weeks of delivery.